A Nd6 molecular butterfly: a unique all-in-one material for SMM, MCE and maiden photosensitized opto-electronic device fabrication. Issue 4 (7th January 2022) - Das, Krishna Sundar; Saha, Sayan; Pal, Baishakhi; Adhikary, Amit; Moorthy, Shruti; Bala, Sukhen; Akhtar, Sohel; Ghose, Pradeepta Kumar; Singh, Saurabh Kumar; Ray, Partha Pratim; Mondal, Raju
Abstract : We report herein an aesthetically pleasing hexanuclear Nd6 molecular butterfly using a rather nonconventional N-rich pyridyl-pyrazolyl based ligand and their concomitant SMM and MCE properties along with elusive electronic properties. Abstract : Besides iron, ironically neodymium (Nd) is the most ubiquitously used metal for magnetic purposes, even among the lanthanides, when it comes to the field of molecular magnetism, yet it ranks among the least studied metals. However, strong apathy towards this magnetic lanthanide means that vital information will be missed, which is required for the advancement of the subject. Herein, we have successfully demonstrated the usefulness of a hexanuclear neodymium complex as a magnetic material, and also in electronic device fabrication. A NdIII6 cage with an aesthetically pleasing butterfly topology was synthesized using a rather non-conventional N-rich pyridyl-pyrazolyl based ligand. The cage shows single molecule magnet (SMM) properties, with an effective energy barrier, U eff, value of 3.4 K and relaxation time, τ 0, of 3.1 × 10 −4 s, originating from an unusual occurrence of metal centres with different coordination environments. Furthermore, magnetic studies reveal significant cyrogenic magnetic cooling, with a magnetic entropy change of 8.28 J kg −1 K −1 at 5 T and 3 K. To the best of our knowledge, the titular compound is the only example of a Nd-complex that exhibits concomitant magnetocaloric effect (MCE) and SMM properties. Complete active space self-consistent field (CASSCF) calculations were carried out to shed light on the origin of the magnetic anisotropy and magnetic relaxation of the compound. The same uniqueness is also true for the first electronic investigation carried out on the Nd complex. The maiden electronic device fabricated using the Nd complex shows an interesting intertwining of electronic and optical features, which contribute towards its improved photosensitized optoelectronic data.